Analisis Peran Grup “Info Cegatan Jogja” dalam Upaya Penyelesaian Permasalahan Tarif Parkir “Nuthuk” di DIY - Miftahul Ahsan, Muhammad; Permatasari, Ane (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
Info Cegatan Jogja (ICJ) group or community has an important role in the lives of the people of Yogyakarta as a place to discuss, interact, and convey aspirations through social media posts. Of the various types of posts in ICJ, one of the posts that is still often found is posts related to the issue of